PEMBERDAYAAN PENDIDIKAN TEKNIK BUSANA DI PERGURUAN TINGGI UNTUK PENGEMBANGAN INDUSTRI GARMEN DI PASAR GLOBAL - Noor Fitrihana (LPMPP Universitas Negeri Yogyakarta, 2005)
Indonesian garment industries have been sluggishness. Since economic crisis incoming, Indonesian garment products loose ofthe competitiveness until now. In the last five years, perfonnance oftextile industry got decrease because many domestic probleIIĺ. The problems are skills ofworkforce, out ofdate technology and poor of-fashion product inovation. Facing the global market ifnot good plan anticipate, gannent industries are cannot running growthand become sunset industry. To solve the problems, one of the ways is empowennent higher education institutions have links with them. That one is fashion design department in university. Market trend for the future is on